(untitled) (The Review of Diabetic Studies, 2022)
OBJECTIVES: Aronia melanocarpa (Aronia) is a shrub with small berries, chokeberries. Chokeberries are claimed to possess health benefits due to a high content of polyphenols. Aronia is known to be extremely antioxidant; however, evidence for its health benefits is not established. This review gives an overview of the impact of Aronia on cardiometabolic risk factors and diseases. METHODS: Seventeen studies on cardiometabolic risk factors and diseases were identified through a systematic search on PubMed, Embase, and Cochrane. Inclusion criteria were studies with Aronia as intervention, performed in individuals with cardiometabolic disease or risk factors, e.g., type 2 diabetes (T2D), cardiovascular disease, hypertension, dyslipidaemia, impaired glucose tolerance, overweight, central obesity and smoking. Four of these studies were applicable for a quantitative analysis. RESULTS: Aronia did not influence body weight, circulating triglycerides, total cholesterol, high-density lipoprotein (HDL) cholesterol, or blood pressure. The quantitative analysis revealed a mean reduction in blood glucose of 0.44 mmol/l (P=0.0001) in the treatment group compared with the control group suggesting that Aronia treatment may have a beneficial impact on blood glucose. In addition, treatment durations of 6 weeks to 3 months tended to decrease low-density lipoprotein (LDL) cholesterol, while shorter treatment durations had no effect on LDL cholesterol. The quantitative analysis did not provide data on long-term effects of Aronia on lipids. CONCLUSIONS: More long-term high-quality randomized controlled studies are needed to clarify if dietary supplementation with Aronia has beneficial effects on cardiometabolic diseases.